2013
DOI: 10.1248/cpb.c13-00547
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Selected Nitropolycyclic Aromatic Hydrocarbons in Water Samples

Abstract: A new method for the analysis of selected nitropolycyclic aromatic hydrocarbons (NPAHs) at ultra-trace levels in water samples is proposed. Particulate NPAHs were collected on a GC glass fiber filter. Soluble NPAHs were collected on a C18 Empore disk. After simple clean-up and concentration of NPAHs in both phases, the NPAHs were analyzed using HPLC equipped with clean-up, reducer, concentration and chemiluminescence detection units. The proposed method showed good linear calibration curves with correlation co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…Until now, the studies of NPAHs are mainly focused on sediment, soil, and atmosphere [31][32][33][34]. Because NPAHs are at trace levels in the water, the study of NPAHs in water environment are rare.…”
Section: Comparison With Other Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Until now, the studies of NPAHs are mainly focused on sediment, soil, and atmosphere [31][32][33][34]. Because NPAHs are at trace levels in the water, the study of NPAHs in water environment are rare.…”
Section: Comparison With Other Methodsmentioning
confidence: 99%
“…Because NPAHs are at trace levels in the water, the study of NPAHs in water environment are rare. A few works have tried to extract nitro-PAHs using SPE and SPME [18,20,[31][32][33]35]. LLE with dichloromethane or hexane has also been used to extract NPAHs from the water sample [19].…”
Section: Comparison With Other Methodsmentioning
confidence: 99%
“…In addition to the mentioned process, these compounds may also enter into aquatic environments through industrial and domestic sewage effluents, exhaust of gasoline and diesel combustion engines, industrial discharges and wastewater treatment plants and especially from spillage of petroleum and petroleum products [8]. Although a recent study reported pg L -1 to ng L -1 levels of nitro-PAHs derivatives in lake and river water samples [7,[9][10][11][12], information regarding of nitrated and oxygenated PAHs contents in aquatic samples is limited. As a consequence, research devoted to understand the behavior of PAHs derivatives, concentrations in water compartments, sources and occurrence, mutagenic and carcinogenic activities, has recently gained importance, and the development of analytical methods for identification and quantification is crucial for the above mentioned purposes.…”
Section: Introductionmentioning
confidence: 99%
“…These compounds can have 100,000 times more mutagenic and 10 times more carcinogenic characteristics than PAHs [4,5]. The International Agency for Research of Cancer (IARC) has classified some nitro-PAHs as belonging to 2A group (probably carcinogenic to humans), such as 1-nitropyrene and 6-nitrochrysene, and 2B group (possibly carcinogenic to humans) compounds like 2-nitrofluorene, among others [6][7][8].…”
Section: Introductionmentioning
confidence: 99%